External Auditory Canal: Computed Tomography Analysis and Classification - El-Anwar, Mohammad Waheed; Fouad, Yasser Ahmed; Elgohary, Ahmed Fouad; Saber, Sameh; Mobasher, Mohamed Adel (International Archives of Otorhinolaryngology, 2023)
Introduction Computed tomography (CT) details of the external auditory canal (EAC) are not fully covered in the literature, so building up base for the CT evaluation and description is important. Preoperative details of the EAC are mandatory before any approach or procedure involving the canal.Objective To determine the different dimensions, measurements, and grading of the EAC by CT scan that were not previously published.Methods The CT scans of 100 temporal bones (200 sides) were included. Axial images were acquired with multiplanar reformates to obtain delicate details in coronal and sagittal planes for all subjects.Results At the EAC entry, the mean vertical length (height) was 7.75 ± 1 mm, and its mean horizontal length (width) was 6.1 ± 0.8. At the bony cartilaginous junction of the EAC, the mean vertical length was 7.88 ± 1 mm, and its mean horizontal length was 6.22 ± 0.9. At the EAC isthmus, the mean vertical length was 6.8 ± 0.97 mm, and its mean horizontal length was 5.2 ± 0.76. At the medial end of the EAC, the mean vertical length was 7.1 ± 0.9 mm, and its mean horizontal length was 5.4 ± 0.85. There were no reported significant differences between right and left sides in all dimensions. Males showed significantly longer vertical and horizontal dimensions of the EAC entry, vertical dimension of the isthmus, and vertical dimension of the medial end of the EAC than females.Conclusion This study improves otologists and radiologists' awareness of EAC variations in the ear field and can be of help to residents in training.
Keywords: external auditory canal; ear; computed tomography; isthmus; endoscopic ear surgery